Analysis of ASEAN’s Role as an International Organization in Addressing Human Trafficking Cases in Cambodia - Yasmin Zahra; Widia Yulianti; Betsaida Lasmiari Purba; Prihandono Wibowo; Muhammad Indrawan Jatmika (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2026)
This analysis discusses ASEAN as an international organization that responds to and addresses human trafficking cases in Cambodia. Human trafficking occurs due to various factors—poverty, political instability, and limited job opportunities. This analysis employs a qualitative, descriptive approach. Data collection was conducted through literature review, where the author accessed various secondary sources such as scientific journals, books, and articles from reputable media outlets. Kelly Kate Pease’s theory of international organizations serves as the primary analytical framework, particularly regarding ASEAN’s three roles: Problem Solver, Aid Provider, and Capacity Builder. Through the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP), ASEAN plays a crucial role in policy formulation and cross-border collaboration to address human trafficking issues. Additionally, ASEAN plays a role in providing assistance and rehabilitation support for victims through various frameworks such as the TIP Bohol initiative and the ASEAN Multi-Sectoral Work Plan Against Trafficking in Persons (TIP). ASEAN strives to find regional solutions to eradicate human trafficking in the region; in Cambodia, human trafficking poses a significant threat and disrupts ASEAN’s security stability. Keywords: Human Trafficking, ASEAN, ACTIP, Cambodia